Bibliometric Analysis of the Convergence of Sustainability and Financial Reporting - Judijanto, Loso (West Science Social and Humanities Studies, 2025)
The convergence of sustainability and financial reporting has emerged as a pivotal theme in corporate transparency, accountability, and long-term value creation. This study conducts a comprehensive bibliometric analysis to explore the intellectual structure, thematic evolution, and global collaboration trends within this interdisciplinary field. Using data extracted from the Scopus database for the period 2000–2024, and analyzed through VOSviewer software, the study maps key research clusters, influential authors, dominant keywords, and country-level partnerships. Results reveal that sustainability reporting serves as the central node linking multiple thematic areas, including integrated reporting, corporate governance, and non-financial disclosures. Recent trends show a growing focus on sustainable development and green accounting, reflecting a shift from conceptual models to more impact-driven reporting strategies. Co-authorship networks demonstrate strong intellectual integration among leading scholars, while country collaboration maps highlight the growing influence of emerging economies like China and Saudi Arabia. This analysis contributes to the field by synthesizing fragmented literature, identifying research hotspots, and proposing future directions for scholars, practitioners, and policymakers seeking to enhance the credibility and relevance of corporate reporting in the sustainability era.